TANGGUNG JAWAB HUKUM ARSITEK TERHADAP KONSTRUKSI BANGUNAN YANG TIDAK SESUAI DENGAN PERENCANAAN - Ni Made Trisna Dewi (Kerta Dyatmika, 2019)
In line with the Government's efforts to improve development in all areas, the built-up aspect of housing development continues to grow rapidly. Environmental problems that threaten and greatly endanger human life has been the emergence of threats and greater danger, so people began to learn the secrets of natural ecosystems and rules of order, to correct all mistakes and errors of attitude and actions of wrongdoing, also to prevent errors Furthermore. Architects perform the stages of the job. Ideally all the above stages are done for various types of buildings, from residential buildings to complex buildings of skyscrapers. Given the complexity of design and heavy responsibility, it is clear that the practice of architects can not be done by any expert. The expert must have an architectural education background, work experience (the more experience the higher his or her skills) and professional competence. These are the things that must be legally recognized through the Law-Ars. Recognition of the profession of architects. This is what prompted the authors interested in writing research with the title "Responsibility of the Right Architects Against Construction Buildings That Do Not Match With Planning. The type of research used is normative research because in this study besides based on existing theories then also compared those theories with existing circumstances on the responsibility of the architect's right to construct construction that is not in accordance with the planning. the approaches used in this legal research are the approach of the law and the conceptual approach. The results of the above discussion and analysis can be made as follows: The authority of the architect in supervising the course of development In general, Architect is an expert who mastered in the field of architectural science, design experts or environment experts built. The term architect is often defined narrowly as a building designer, is one who is involved in planning, designing and supervising the construction of a building, whose role is to guide decisions affecting aspects of the building in terms of architect, culture, or social problems and the architect's responsibility to the construction of the building which is not in accordance with the planning of some legal experts have tried to explain that errors generally consist of intentional, negligent and accountable criminals. Keywords: Responsibility, Architects and Building Construction